Factores de riesgo y su relación con la enfermedad renal crónica en pacientes atendidos en el Hospital Martín Icaza, junio – octubre 2023. - Burbano Hurtado, Madeline Xiomara (2023)
Chronic kidney disease has become a serious public health problem. There are currently more than 1.4 million patients receiving renal replacement therapy worldwide. One way to reduce the economic burden of chronic kidney disease would be early intervention. There are multiple risk factors exposed in the literature, such as: the genetic and phenotypic composition of an individual. Factors such as race, sex, age, and family history are very important. In addition, smoking, obesity, hypertension, and diabetes mellitus can also lead to kidney diseases. Aim: Determine the risk factors and their relationship with chronic kidney disease in patients treated at the Martín Icaza Hospital, June – October 2023. Methodology: The research will employ a quantitative approach. Also, it is analytical and documentary, since all scientific evidence will be based on information from indexed journals and scientific articles obtained from search engines such as PubMed, Cochrane, and Google Scholar. Results: The main risk factors in patients at the Martín Icaza Hospital include High Blood Pressure and Diabetes Mellitus, as well as lack of knowledge about the necessary care. Chronic Kidney Failure mainly affects adult men and is a silent degenerative disease. The lack of education, knowledge of the disease and economic resources influence the patient's self-care.